A Comparison of Adolescents Consumption of Micro and Macro Nutrient Rich Foods - Hamilton-Ekeke, Joy-Telu (International Journal of Child Health and Nutrition, 2013)
The study involves a comparison of pupils’ consumption of macro and micro nutrient rich food as well as healthy and less healthy snacks after being exposed to a teaching model on balanced diet developed by the researcher which takes into cognisance pupils’ prior knowledge of healthy eating. Healthy snacks are snacks that are low in fat and sugar while less healthy snacks are snacks that are high in fat and sugar. The study was carried out in Britain, United Kingdom in summer term of 2007. Participants were year 7 pupils of Ceredigion Local Education Authority in rural Mid-Wales, they were requested to fill-in a Food Diary of food consumed at breakfast, lunch and dinner times including mid-morning and mid-afternoon snacks for five days (Thursday to Monday). This is to include both food consumed at home at weekend as well as school meals consumed at school during weekdays. There was evidence of increase of consumption of healthy snack as well as the consumption of macro nutrients (carbohydrate, fat and protein) and micro nutrients (vitamin, mineral and fibre); all six classes of food that makes up a balanced diet [1] after the intervention compared to before the intervention, although the rate of increase in the consumption of micro nutrient was not statistically significant compared to the increased in the consumption of macro nutrient. This study revealed that though the teaching model was able to alter eating behaviour in the desired direction of healthy eating which is the consumption of micro nutrient. More has to be done to encourage adolescents to consume more vitamin, mineral and fibre rich food items.